Dialdehyde xanthan gum and curcumin synergistically crosslinked bioprosthetic valve leaflets with anti-thrombotic, anti-inflammatory and anti-calcification properties. (15th June 2023) - Hu, Mengyue; Peng, Xu; Shi, Shubin; Wan, Chang; Cheng, Can; Yu, Xixun
Abstract: Currently commercial glutaraldehyde (GA)-crosslinked bioprosthetic valve leaflets (BVLs) suffer from thromboembolic complications, calcification, and limited durability, which are the major stumbling block to wider clinical application of BVLs. Thus, developing new-style BVLs will be an urgent need to enhance the durability of BVLs and alleviate thromboembolic complications. In this study, a quick and effective collaborative strategy of the double crosslinking agents (oxidized polysaccharide and natural active crosslinking agent) was reported to realize enhanced mechanical, and structural stability, excellent hemocompatibility and anti-calcification properties of BVLs. Dialdehyde xanthan gum (AXG) exhibiting excellent stability to heat, acid-base, salt, and enzymatic hydrolysis was first introduced to crosslink decellularized porcine pericardium (D-PP) and then curcumin with good properties of anti-inflammatory, anti-coagulation, anti-liver fibrosis, and anti-atherosclerosis was used to synergistically crosslink and multi-functionalize D-PP to obtain AXG + Cur-PP. A comprehensive evaluation of structural characterization, hemocompatibility, endothelialization potential, mechanical properties and component stability showed that AXG + Cur-PP exhibited better anti-thrombotic properties and endothelialization potential, milder immune responses, excellent anti-calcification properties and enhanced mechanical properties compared with GA-crosslinked PP. Overall, this cooperative crosslinking strategy provides a novel solution to achieve BVLs with enhanced mechanical properties and excellent anti-coagulation, anti-inflammatory, anti-calcification, and the ability to promote endothelial cell proliferation. Graphical abstract: Unlabelled Image